Effect of temperature and leaf wetness duration on infection of sweet oranges by Asiatic citrus canker - Dalla Pria, M.; Christiano, R. C. S.; Furtado, Edson Luiz [UNESP]; Amorim, L.; Bergamin Filho, A. (Blackwell Publishing, 2006)
Asiatic citrus canker, caused by Xanthomonas smithii ssp. citri, formerly X. axonopodis pv. citri, is one of the most serious phytosanitary problems in Brazilian citrus crops. Experiments were conducted under controlled conditions to assess the influence of temperature and leaf wetness duration on infection and subsequent symptom development of citrus canker in sweet orange cvs Hamlin, Natal, Pera and Valencia. The quantified variables were incubation period, disease incidence, disease severity, mean lesion density and mean lesion size at temperatures of 12, 15, 20, 25, 30, 35, 40 and 42 degrees C, and leaf wetness durations of 0, 4, 8, 12, 16, 20 and 24 h. Symptoms did not develop at 42 degrees C. A generalized beta function showed a good fit to the temperature data, severity being highest in the range 30-35 degrees C. The relationship between citrus canker severity and leaf wetness duration was explained by a monomolecular model, with the greatest severity occurring at 24 h of leaf wetness, with 4 h of wetness being the minimum duration sufficient to cause 100% incidence at optimal temperatures of 25-35 degrees C. Mean lesion density behaved similarly to disease severity in relation to temperature variation and leaf wetness duration. A combined monomolecular-beta generalized model fitted disease severity, mean lesion density or lesion size as a function of both temperature and duration of leaf wetness. The estimated minimum and maximum temperatures for the occurrence of disease were 12 degrees C and 40 degrees C, respectively.
Keywords: beta function; Citrus sinensis; epidemiology; monomolecular model; Xanthomonas axonopodis pv. citri; Xanthomonas smithii ssp citri